Derivation of switching angles of the cascaded multilevel voltage source inverter subjected to a new pulse width modulation scheme - Zainal, Salam, Dr.; Junaidi, Aziz (The Institution of Engineers, Malaysia, 2011)
Link to publisher's homepage at http://www.myiem.org.my/